Tiga Merek, Satu Pasar: Analisis Aktivitas Komunikasi Korporat Cokelat di Indonesia - Audy Salsabillah; Diah Puspita Sari; Rini Sudarmanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of the chocolate industry in Indonesia has prompted chocolate companies to compete intensively in corporate communication strategies, particularly through digital media platforms. This study aims to examine digital communication patterns and the level of social media activity of three chocolate brands in Indonesia: SilverQueen, Cadbury Dairy Milk Indonesia, and Snickers Indonesia using a qualitative approach. Through systematic observation over fourteen days across Instagram, Facebook, TikTok, YouTube, and X, this research identified content categories, posting frequency, and public response patterns for each brand. Findings indicate that Snickers Indonesia and Cadbury Dairy Milk Indonesia demonstrate higher levels of digital activity with 58 and 41 posts respectively, utilizing diverse content types including promotions, collaborations, contests, relatable moments, and follower interactions. In contrast, SilverQueen showed minimal activity with only 4 posts, limited to Instagram and Facebook with primarily relatable content and follower engagement. Analysis reveals that communication patterns combine one-way information dissemination, interactive dialogue, and mass media distribution strategies. Instagram emerged as the platform with the highest public response, particularly for Snickers Indonesia during their K-Pop brand ambassador campaign collaboration. The research concludes that digital communication intensity and content variety correlate significantly with public engagement and brand loyalty, positioning Snickers Indonesia and Cadbury Dairy Milk Indonesia in a more strategically advantaged position (Quadrant B) compared to SilverQueen (Quadrant C) in corporate communication strategy. These findings underscore the importance of consistency, content creativity, and integrated digital platform management in maintaining competitive advantage in the digital era.